CLEC3B Expression in Saliva and Serum: A Promising Biomarker Approach for Oral Squamous Cell Carcinoma: CLEC3B Expression in Saliva and Serum: Oral Squamous Cell Carcinoma - Ahmed, Syeda Zehra; Usman, Shumaila; Shaikh, Fouzia; Butt, Atif Iqbal; Zareef, Uzma; Sani, Aliya Irshad (Pakistan Journal of Health Sciences, 2025)
Metastasis, considered the most important factor for determining the survival rate of oral squamous cell carcinoma (OSCC). Therefore, a useful biomarker is needed to classify patients with OSCC in order to ensure effective treatment. Although CLEC3B has been mentioned in the literature, its relationship to OSCC has not yet been studied. Objectives: To evaluate the potential of CLEC3B expression in saliva and blood as a diagnostic biomarker for oral squamous cell carcinoma. Methods: A case-control study comprised of 80 samples (40 blood and 40 saliva) from 40 participants was conducted. Both Ziauddin University Hospital and Abbasi Shaheed Hospital served as the recruitment sites for all samples. RT qPCR was used to determine the expression levels of CLEC3B in OSCC and healthy individuals after obtaining written informed consent. Ziauddin University Ethical Review Committee approved this project. SPSS version 20.0 was used to analyze the data. Results: When compared to healthy people, OSCC patients' saliva had considerably lower levels of CLEC3B (p-value 0.001). Moreover, the expression was comparatively lower in the saliva of OSCC patients as compared to blood, suggesting that this marker can be better evaluated in saliva. Conclusions: Low expression of CLEC3B with the progression of OSCC depicts its tumor suppressive role in the tumor microenvironment. Its high yield in saliva can make it a suitable and easily assessable biomarker for determining OSCC progression.